From nano to micro: evolution of magnetic domain structures in multidomain magnetite - Nagy,L; Williams,W; Tauxe,L; Muxworthy,AR (Geochemistry, Geophysics, Geosystems, 2019)
Reliability of magnetic recordings of the ancient magnetic field is strongly dependent on the magnetic mineralogy of natural samples. Theoretical estimates of longterm stability of remanence were restricted to singledomain (SD) states, but micromagnetic models have recently demonstrated that the socalled singlevortex (SV) domain structure can have even higher stability that SD grains. In larger grains ( urn:x-wiley:ggge:media:ggge21913:ggge21913-math-000110 μm in magnetite) the multidomain (MD) state dominates, so that large uniform magnetic domains are separated by narrow domain walls. In this paper we use a parallelized micromagnetic finite element model to provide resolutions of many millions of elements allowing us, for the first time, to examine the evolution of magnetic structure from a uniform state, through the SV state up to the development of the domain walls indicative of MD states. For a cuboctahedral grain of magnetite, we identify clear domain walls in grains as small as ∼3 μm with domain wall widths equal to that expected in large MD grains; we therefore put the SV to MD transition at ∼3 μm for magnetite and expect welldefined, and stable, SV structures to be present until at least ∼1 μm when reducing the grain size. Reducing the size further shows critical dependence on the history of domain structures, particularly with SV states that transition through a socalled “unstable zone” leading to the recently observed hardaligned SV states that proceed to unwind to SD yet remain hard aligned.